ELECTORAL VIOLENCE AND THE AFRICAN CONSCIENCE - Ondigo, Anne Celestine Achieng (Asian Horizons, 2016)
There is a contradiction between electoral violence taking place in Africa and the values central to an African Christian conscience. The new phenomenon triggering civil wars in Africa is electoral violence. The violence has direct impact on civilians. During the violence, people lose lives, property worth millions is destroyed, internally displaced persons emerge, yet others flee the country as refugees. The war is usually politically polarizing in pluralistic societies making it ethnic in nature. Once the violence breaks out, the war is fought by all including Christians who turn against each other. Using the judgmental and legislative conscience of the African Christian, can conscience address the problem of electoral violence in Africa and how can this be done?